2016
DOI: 10.1097/sap.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

The Superior Rectal Artery as a Recipient Vessel for Free Flap Transfer After Partial Sacrectomy in Patients With Chordoma

Abstract: Free flaps have rarely been used to reconstruct lumbosacral defects, primarily because of the lack of suitable recipient vessels in this region. We propose the novel use of the superior rectal artery as a recipient vessel for free flap transfer after partial or total sacrectomy. We transferred free flow-through latissimus dorsi musculocutaneous flaps, with the superior rectal vessels as recipient vessels, to reconstruct defects after partial sacrectomy in 2 patients with sacral chordoma. The flaps survived com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…It was observed that free flaps can provide greater flap volume and greater freedom of flap placement than regional flaps, and they make the obliteration of dead space and tensionfree wound closure possible. 9 The flap that fits the defect in size and shape can be transferred, and the suture lines can be simplified without interference with donor site closure. We believe that these tages of free flaps can provide reliable wound coverage for oncologic gluteal defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed that free flaps can provide greater flap volume and greater freedom of flap placement than regional flaps, and they make the obliteration of dead space and tensionfree wound closure possible. 9 The flap that fits the defect in size and shape can be transferred, and the suture lines can be simplified without interference with donor site closure. We believe that these tages of free flaps can provide reliable wound coverage for oncologic gluteal defects.…”
Section: Discussionmentioning
confidence: 99%
“…15 With regard to the free flap donor site, the latissimus dorsi flap was determined to have several advantages, making it the flap of choice for gluteal reconstruction. 9,11,16 The main advantage is that the shape and volume of the flap can be easily tailored to meet the requirements of an individual defect. The second advantage is that the flaps can be harvested using a 2-team approach with the patient in either prone or lateral decubitus position, as the donor site is distant from the recipient site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Free flaps can be an alternative option, allowing the use of distant flaps such as ALT or even latissimus dorsi. However, the increased surgical complexity and the challenge of finding recipient vessels in a previously irradiated wound site limit their use 38 . The 2 cases that required free flaps did not increase the mean operating time.…”
Section: Discussionmentioning
confidence: 99%